Neuropatia autonomica cardiaca en diabetes - Aguilar Aguilar, Madelaine Carolina (Machala : Universidad Técnica de Machala, 2020)
Diabetes mellitus is a disease characterized by a whole of metabolic disorders and eventually produce a serie of organic complications, which the heart being one of the major organs affected; Currently has a high prevalence worldwide, Objective To verify the epidemiology of cardiac autonomic neuropathy, To determine cwhich are the most recommended diagnostic methods for cardiac autonomic neuropathy, To analyze how known is cardiac autonomic neuropathy as a complication of diabetes mellitus, Methods Is a systematic, retrospective, qualitative, descriptive, cross-sectional review to know which one is the diagnostic method more efficient to diagnose cardiac autonomic neuropathy in diabetes. Conclusions Cardiac autonomic neuropathy is a very poorly diagnosed complication of the diabetes mellitus and can be deadly. There are a number of tools for diagnosis the cardiac autonomic neuropathy which we can use, starting with the risk factors; Futher, we can use some laboratory tests; Sleep quality tests and tests of cardiac autonomic function which are one of the diagnostic bases that we have at the moment of the medical consultation with diabetic patients to use to diagnose the cardiac autonomic neuropathy
La diabetes mellitus es una patología que se caracteriza por un conjunto de desordenes metabólicos que afectan al páncreas y a la larga provoca una serie de complicaciones orgánicas, siendo el corazón uno de los órganos mayor afectados; ahora, presenta una alta prevalencia a nivel mundial,Objetivos: Constatar la epidemiología de la neuropatía autonómica cardiaca, Determinar cuáles son los métodos diagnósticos más recomendables para la neuropatía autonómica cardiaca, Analizar cuán conocida es la neuropatía autonómica cardiaca como complicación de la diabetes mellitus, Materiales y Métodos: Es una revisión sistemática, de tipo retrospectivo, cualitativo, descriptivo, transversal para conocer cual es el método diagnóstico más eficiente para diagnosticar la neuropatía autonómica cardiaca en diabetes. Conclusión: La neuropatía autonómica cardiaca es una complicación muy poco diagnosticada de la diabetes mellitus y que puede llegar a ser mortal. Existen para su diagnóstico una serie de herramientas que podemos usar, empezando con los factores de riesgo; adicional a eso, también nos podemos ayudar con pruebas de laboratorio; pruebas de la calidad del sueño y pruebas de función autonómica cardiaca que son una de las bases diagnósticas con las que contamos al momento de encontrarnos en consulta con pacientes diabéticos que puede que padezcan además de neuropatía autonómica cardiaca.
Keywords: NEUROPATIA AUTONOMICA CARDIACA; DIABETES MELLITUS; PRUEBAS DE FUNCION AUTONOMICA